1998
DOI: 10.1021/ac980800g
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical Investigation of Acrylodan-Labeled Mutant Phosphate Binding Protein

Abstract: The static and dynamical behavior of a fluorescently labeled mutant of the Escherichia coli periplasmic phosphate binding protein (PBP) was investigated through steady-state and time-resolved fluorescence spectroscopy. As a means of developing a biorecognition element for inorganic phosphate (P(i)), alanine-197 of PBP was replaced with a cysteine. This site was then labeled with an environmentally sensitive fluorophore. The fluorescence emission of the mutant PBP labeled with acrylodan (MPBP-AC) proved to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Similar work performed in our laboratory in the rational design of a sensing system for calcium also pointed to the same reason regarding the behavior of the probes (21,22). In addition, we have also studied the structure and dynamics of a mutant form of the phosphate-binding protein that was site specifically labeled with MDCC (23). We conclude that the quenching of the fluorescence signal seen in this study is a result of the probe being more exposed to the solvent or a hydrophilic environment when the protein binds glucose.…”
Section: ϫ4supporting
confidence: 66%
“…Similar work performed in our laboratory in the rational design of a sensing system for calcium also pointed to the same reason regarding the behavior of the probes (21,22). In addition, we have also studied the structure and dynamics of a mutant form of the phosphate-binding protein that was site specifically labeled with MDCC (23). We conclude that the quenching of the fluorescence signal seen in this study is a result of the probe being more exposed to the solvent or a hydrophilic environment when the protein binds glucose.…”
Section: ϫ4supporting
confidence: 66%
“…Studies of intrinsic tryptophan quenching in NBP upon binding to a ligand also demonstrated a strong response to cobalt [22]. The remaining metals all showed less maximum quenching than nickel and detection limits were more than 10 to 100 times higher than for nickel.…”
Section: Discussionmentioning
confidence: 93%
“…A number of E. coli periplasmic binding proteins have been utilized for the development of potential biosensors for phosphate (22)(23)(24), glucose (25,26), and maltose (27). Due to the favorable sensitivity and specificity for glutamine, GlnBP was selected as the basis for the optical biosensor.…”
Section: Resultsmentioning
confidence: 99%